Anatomy teaching and learning in Malaysia during the COVID-19 pandemic - Tg Muda, Tg Fatimah Murniwati; Rushaidhi, Madihah; Choy, Ker Woon; Dhamodharan, Jagadeesh; Abdul Ghafar, Norzana; Wong, Kah Hui; Abas, Razif; Teoh, Seong Lin; Hadie, Siti Nurma Hanim (Penerbit Universiti Sains Malaysia, 2021)
The abrupt transition from face-to-face to online anatomy teaching amidst the COVID-19 pandemic has posed great challenges to anatomy lecturers in Malaysia, as they have had to adapt to new skills to prepare and deliver online classes. These online classes were delivered either synchronously via a web teleconferencing application or asynchronously through pre-recorded videos that were uploaded to the learning management system (LMS). The online delivery of anatomy practical classes has become a major concern among anatomy lecturers and students, especially in public institutions, as there is a lack of hands-on experience and social interaction. Nevertheless, some private medical schools have adapted well to both online lectures and practical classes, as they had been venturing towards online learning and virtual reality tools even before the pandemic commenced. The Malaysian Anatomical Association (MAA) webinar, “Transformation of Anatomy Education in Malaysia during COVID-19 Pandemic”, discussed the issues related to lecturers’ and students’ receptivity to online anatomy classes. This study discusses the issues related to online anatomy teaching and learning (T&L) and the actions taken by the university’s governance and anatomy faculty members to resolve the issues discussed in the academic discourse.